Mebulle Bai: Ritual, Ruang Bersama, dan Rekonsiliasi Masyarakat Lokal di Mamasa, Sulawesi Barat - Stepanus Stepanus; Izak Y.M. Lattu; Tony Tampake (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2019)
The establishment of Mamasa as a district adds diversity and escalation of conflict which often occur not only in the form of fights or physical clashes, but also of differences in perception. This situation is exacerbated by the governance of conflict which tends to use judicial or repressive approach. An approach that only pays attention to rules and punishments without trying to build sustainable peaceful relations in society. The research objective to be achieved in this paper is to describe and analyze the Mebulle Bai Ritual as a shared space in solving the social conflict of the Mamasa community. The implementation of the Mebulle Bai Ritual is a symbolic act intended to restore the relations of various parties in the conflict. Restoring relationships in conflict is aimed at resolving the conflict as well as all parties, such as family and society. This approach is based on a common understanding that conflict could break relation of the conflicting parties and contribute to destroy harmony in society. Therefore, recovery is a comprehensive process supported by the presence of various parties in building peace. The result achieved is the Mebulle Bai ritual which can be ruled as a shared space in resolving conflicts because they contain the values of justice, equality and humility. Each party is equally enforced, regardless of their religious, ethnic, cultural, racial and social status in society.